2014
DOI: 10.1021/am5010943
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Li2O2 Growth and Its Effect on Kinetics of Li–O2 Batteries

Abstract: Lithium peroxide (Li2O2), the solid and intrinsically electronic insulating discharge product of Li-O2 batteries strongly influences the discharge and charge kinetics. In a series of experiments, we investigated the growth of Li2O2 upon discharge and the corresponding reduction and oxidation processes by varying the depth of discharge. The results indicate that insulating Li2O2 particles with a disc-like shape were formed during the initial discharge stage. Afterward, the nucleation and growth of Li2O2 resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 50 publications
12
120
5
Order By: Relevance
“…For the influence of electrode morphology, previous studies have reported that carbon nanotubes and granular KB carbon can both produce toroidal Li 2 O 2 . The morphology of electrode material is not the critical factor to determine its discharge characteristic 9, 47. Our recent study also reported that flower‐like Li 2 O 2 assembled by Li 2 O 2 sheets was both produced on Ni/Co 3 O 4 nanowires and Ni/Co 3 O 4 rectangular nanosheet electrodes 48.…”
Section: Resultsmentioning
confidence: 92%
“…For the influence of electrode morphology, previous studies have reported that carbon nanotubes and granular KB carbon can both produce toroidal Li 2 O 2 . The morphology of electrode material is not the critical factor to determine its discharge characteristic 9, 47. Our recent study also reported that flower‐like Li 2 O 2 assembled by Li 2 O 2 sheets was both produced on Ni/Co 3 O 4 nanowires and Ni/Co 3 O 4 rectangular nanosheet electrodes 48.…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that low current densities and high water concentrations (hundreds to thousands of ppm) both promote the growth of biconcave disks [23,37,[45][46][47]. Similar biconcave disks have also been observed in the precipitation of silicates [48] and corn starch [49], suggesting that there may be a common growth mechanism.…”
Section: The Discharge Productmentioning
confidence: 72%
“…Similar biconcave disks have also been observed in the precipitation of silicates [48] and corn starch [49], suggesting that there may be a common growth mechanism. It has also been reported that the characteristic size of these particles decreases with increasing current densities, and that at sufficiently high rates the deposit forms a conformal film rather than discrete particles [23,37,45,47]. However, it has been suggested that the putative conformal films produced at high currents are in fact carpets of nano-scale needles [39].…”
Section: The Discharge Productmentioning
confidence: 99%
“…A parallel X-ray beam in size of 100 μm diameter was directed on to the samples and diffraction intensities were recorded on large 2D image plate during exposure time. Li 2 O 2 was quantified in the cathodes after discharge using a colorimetric method previously reported by Schwenke et al 39 Briefly, discharged cathodes were first immersed in water then aliquots were taken and added to 2% aqueous solution of TiOSO 4 . Instantaneously a color change occurred and the absorbance spectra of the solutions were collected using a UV-Vis spectrophotometer (Gamry UV/Vis Spectro-115E).…”
Section: Methodsmentioning
confidence: 99%